Simulación de los procesos en el área de producción de la empresa "Maquinarias para el Agro Cia Ltda." (MAQGRO), empleando tecnología CAD - Cabezas Chanalata, Carlos Roberto (2018)
The present research project is focused for the company MAQGRO Ltda., Radica in a technological development where the objective is an improvement in the distribution in plant; MAQGRO Ltda., It is located in the city of Quevedo., It has 25 employees and is in charge of the production of agroindustrial machines for the agricultural and industrial sector. The collection of information about the changes that take place within the company, the results obtained and other adjustments in the proposed topic, it is necessary to carry out and rethink a design study of productive systems, in which the results can be positively adapted within the company; When executing this study, it can be evidenced in the improvement in the production line of improvement in the plant design through the implementation of a simulation software. The main focus of the technological development, that is to say, the distribution in plant of the company, because the update of the process does not have a continuous line of production, nor is it specific in its work areas, so that the generation of times idlers has a high level of presence within the operations, therefore, the establishment of standard times within each operation in null. The final result does not have any document in which all the studies carried out in the company can be collected, in order to provide the necessary information about the problem, the solution and the pertinent recommendations to avoid it in the future. To reach the expected result, it is necessary to follow an established methodology, which will be explained throughout the work